A history of the expansion of Christianity ; v. 2 the thousand years of uncertainty - Latourette, Kenneth Scott 1884-1968 (Exeter, UK Paternoster, 1971)
Includes bibliographical references and index.
First published 1938, Harper and Row, Publishers, New York.
Keywords: Church history -- Middle Ages, 600-1500.